Long-Term Adherence and Persistence to Low-Dose Aspirin for the Prevention of Cardiovascular Disease: A Population-Based Cohort Study - Pareen Vora; Montse Soriano-Gabarró; Beth Russell; Henry Morgan Stewart (International Journal of Clinical Practice)
Background and Aim. Adherence and persistence to low-dose aspirin are key to maximising its cardiovascular benefits in patients with a history of cardiovascular disease (CVD) or those at high CVD risk; however, few studies have provided population-based estimates of its long-term (>2–3 years) use. We aimed to determine long-term (up to 10 years) adherence and persistence to low-dose aspirin for primary/secondary prevention of CVD. Methods. Using information from electronic health records in Germany and the United Kingdom (UK) in a common data model, we followed adults with ≥2 low-dose aspirin prescriptions (75–100 mg) during 2007–2018 for up to 10 years. Included individuals had no low-dose aspirin prescriptions in the year before the follow-up started (date of first low-dose aspirin prescription) and ≥12 months’ observation. Adherence was determined using the medication possession ratio (MPR), and persistence was defined as continuous treatment disregarding gaps between prescriptions of <60 days; analyses were undertaken according to indication (primary/secondary CVD prevention). Results. We identified 144,717 low-dose aspirin users from Germany and 190,907 from the UK. Among patients with 5–10 years’ follow-up, median adherence among secondary CVD prevention users was 60% in Germany and 75% in the UK. Among primary prevention users, median adherence was 50% for both countries. Persistence among secondary CVD prevention users was 58.3% at 2 years, 47.0% at 5 years, 35.2% at 10 years (Germany), and 67.5% at 2 years, 58.0% at 5 years, and 46.8% at 10 years (UK). Among primary CVD prevention users, persistence was 52.8% at 2 years, 41.6% at 5 years, 32.1% at 10 years (Germany), 56.3% at 2 years, 45.4% at 5 years, and 33.8% at 10 years (UK). Conclusions. Long-term adherence and persistence to low-dose aspirin are suboptimal; efforts for improvement could translate into a lower CVD burden in the general population.